The Changing Face Of Engineering Education In Kerala : -An Empirical Study At Engineering Colleges In Kerala - Prasanth M. K.; Suresh Kumar N. B; Ajith Sundaram (International Journal of Engineering Research & Technology (IJERT), 2012)
The engineering education in Kerala is undergoing dramatic changes. Around fifteen years back only cream students went for engineering studies. At present students are joining the course not for passion to engineering stream but as a matter of prestige and pressure from external environment. The scenario is not different among the faculty community also in terms of quality erosion. The present study aimed to find out the impact of age group, educational qualification, experience, extend of participation of faculty members and impact of career development programs on the quality of teaching. The most popular career development tool utilized by faculty members in the field of engineering is attending Seminars. It may be due to the fact that it is an easy task. The research revels that the majority of faculty members in the Engineering discipline belong to thirty five years and their basic qualification is B.Tech. Apart from that, attending workshops, faculty development program, participating in national and international conference helps a faculty to increase the quality of teaching. It is viewed that there is reluctance from the part faculty members in participating in career development programmes.